Economic Consequences of Mispredicting Utility - Bruno S. Frey; Alois Stutzer (Center for Research in Economics, Management and the Arts (CREMA), 2004)
Individuals make systematic mistakes in their decisions, because they mispredict utility from choice options. When deciding, extrinsic attributes of choice options are more salient than intrinsic attributes. Adaptation is neglected, recollection of feelings is distorted, decisions are rationalized and wrong intuitive theories of happiness are applied. People overestimate extrinsic attributes and therefore put too much emphasis on acquiring income and gaining status. In contrast, they underestimate intrinsic attributes and devote too little time to their family, friends or hobbies, which lowers their utility level. The theoretical analysis is consistent with an econometric study on commuting decisions using reported subjective well-being data.
Keywords: A12; D11; D12; D84; I31; J22; 330; adaptation; extrinsic/intrinsic attributes; individual decision-making; misprediction; subjective well-being; time allocation